Judicial Independence and the use of Artificial Intelligence in Courts - Drozd, D.O. (Право и государство №2 (99), 2023)
The relevance of the topic of this research lies in the lack of legal papers on the questions of using computer technologies in judicial proceedings. As artificial intelligence (AI) systems con tinue to advance, there is a growing need to address their potential impact on judicial principles. Various countries try to implement AI technologies in judicial dispute resolution, these processes are progressing intensively, but there is still a significant gap in the existing legal literature on this topic. The subject of this paper is the impact of AI systems’ use in courts on judicial independence. The purpose of the study is to examine the implications of AI technologies on judicial inde pendence and explore how adherence to specific criteria can help maintain the autonomy of the judiciary in the digital age. The topic of this research is highly novel due to the nonexis- tence of legal papers dedicated to the problem of this study. While many scholars are focused on judicial independence, considering it a crucial principle for the rule of law, there is a growing number of researchers analyzing the implementation of AI technologies in court. However, these scientific works primarily concentrate on the ways of possible using AI systems in courts and other general questions. However, there are only a few papers devoted to the analysis of legal risks associated with the use of AI systems in courts. This work is the first one that opens the door to further discussions on the assessment of judicial independence in AI-assisted proceedings. The research methods used in this paper are typical for legal studies. By analyzing the relationship between AI technologies and judicial independence, this research seeks to shed light on the potential challenges that arise from the integration of such computer systems into judicial systems. The current work addresses different approaches to defining key features of judicial independence and then proposes a list of specific criteria necessary to ensure judicial independence when utilizing AI systems. The key conclusions of this research contribute to the scholarly discussion on judicial inde pendence criteria and provide two new specific criteria for AI-assisted proceedings. The author suggests that adhering to this list of specific criteria can provide independence for AI systems themselves and for judicial systems in general. By exploring the criteria for safeguarding ju dicial independence in the context of implementing AI technologies, this article aims to offer valuable insights and recommendations for policymakers and stakeholders
Keywords: artificial intelligence; judicial independence; AI in courts; digital courts; independence of courts